The Energy Leviathan: or how U.S. Shales and Brazil Biodiesel Governance Systems Fail to Promote Decentralization, Accountability, Equity, and Society Participation - De Lima, Arnoldo; Toni, Fabiano (European Journal of Sustainable Development, 2018)
Energy resources and their different forms of regulation are critical to sustainable development. Given this perspective, we compare two different energy resources and their governance systems – the Eagle Ford Shale in the U.S. and the Gaucho Biodiesel Pole in Brazil. Despite the differences in terms of the nature of the energy resource, stakeholders, and institutions, both systems perform poorly in terms of governance, defined here as equity, participation, transparency, and accountability. We collected data using semi-structured interviews with stakeholders, participated in public hearings, and archival research. We found patterns that reveal asymmetric power relations amongst stakeholders and institutions, especially the dominance of the energy industry’s agenda, which hinders self-regulatory autonomy of communities and societal participation.